2008
DOI: 10.4269/ajtmh.2008.79.750
|View full text |Cite
|
Sign up to set email alerts
|

Risk Presented by Copernicia prunifera Palm Trees in the Rhodnius nasutus Distribution in a Chagas Disease-endemic Area of the Brazilian Northeast

Abstract: With the aid of live-bait traps, we studied the risk that Copernicia prunifera palm trees, present in both periurban and rural localities of an endemic Brazilian northeast Chagas disease region, represent to domestic infestation by Rhodnius nasutus. In this area, this important vector has been encountered harboring and transmitting Trypanosoma cruzi, the etiologic agent of the American trypanosomiasis, to mammals, possibly including humans. Results indicate that this bug colonizes C. prunifera palm trees of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…These results are corroborated by other studies that reported higher infection rates and colonization during the dry season 13,14,15 . This disparity highlights the need for further longitudinal studies to define optimum timing for vector control insecticide application.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are corroborated by other studies that reported higher infection rates and colonization during the dry season 13,14,15 . This disparity highlights the need for further longitudinal studies to define optimum timing for vector control insecticide application.…”
Section: Discussionsupporting
confidence: 90%
“…These synanthropic animals often invade peridomicile areas using man-made structures, principally wood piles, as shelters, implying that triatomine T. cruzi infection may be taking place in the domestic environment. These small rodents have also been noted in the neighboring town of Jaguaruana 15 . Further studies on these insects' food sources and the distribution of synanthropic animals are needed to understand the disease infection cycle in the locality.…”
Section: Discussionmentioning
confidence: 59%
“…Currently, sylvatic triatomines have drawn the attention of public health authorities because these insects have invaded domiciles and peridomiciles in rural and peri-urban zones of disease-endemic regions, which is probably a consequence of deforestation and alterations in their natural ecotopes. 10 This finding became more evident after the effective control of Triatoma infestans was achieved in countries where this triatomine was the main vector of Chagas disease. Such a change in the epidemiologic scenario has encouraged authorities to realize the importance of secondary vector species for the success of control of disease in disease-endemic areas.…”
mentioning
confidence: 89%
“…Among these environments, the captured samples almost always harbored T. cruzi with an infection level more than 15%, therefore presenting a risk for humans. 9,10,[13][14][15][16] Recently, in addition to T. cruzi , T. rangeli was encountered for the first time in R. nasutus in the state of Ceará, with a natural infection rate of 7.7%. 9 In a recent survey conducted in Jaguaruana, Ceará, R. nasutus infected with T. cruzi were collected in intradomiciliar and peridomiciliar environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation